Pengaruh Kreativitas dan Pengetahuan Kewirausahaan Terhadap Pembentukan Jiwa Wirausaha Muda pada Mahasiswa FE UNIMED - Vini Vizi Br Ginting; Alfha Alzahro; Nazwa Alifia Irsyah Putri; Amanda Gledis Br Ginting; Andi Taufiq Umar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the influence of creativity and entrepreneurial knowledge on the development of entrepreneurial spirit among young people in the digital era, specifically students of the Faculty of Economics, Universitas Negeri Medan. Using a quantitative approach, data were collected through questionnaires and analyzed using SPSS. The results show that both variables, both partially and simultaneously, have a significant influence on the entrepreneurial spirit. Entrepreneurial knowledge prov